Discovery of Graphene‐Water Membrane Structure: Toward High‐Quality Graphene Process. Issue 26 (18th July 2022) - Okmi, Aisha; Xiao, Xuemei; Zhang, Yue; He, Rui; Olunloyo, Olugbenga; Harris, Sumner B.; Jabegu, Tara; Li, Ningxin; Maraba, Diren; Sherif, Yasmeen; Dyck, Ondrej; Vlassiouk, Ivan; et al.
Abstract: It is widely accepted that solid‐state membranes are indispensable media for the graphene process, particularly transfer procedures. But these membranes inevitably bring contaminations and residues to the transferred graphene and consequently compromise the material quality. This study reports a newly observed free‐standing graphene‐water membrane structure, which replaces the conventional solid‐state supporting media with liquid film to sustain the graphene integrity and continuity. Experimental observation, theoretical model, and molecular dynamics simulations consistently indicate that the high surface tension of pure water and its large contact angle with graphene are essential factors for forming such a membrane structure. More interestingly, water surface tension ensures the flatness of graphene layers and renders high transfer quality on many types of target substrates. This report enriches the understanding of the interactions on reduced dimensional material while rendering an alternative approach for scalable layered material processing with ensured quality for advanced manufacturing. Abstract : A study of a newly discovered graphene‐water membrane is accomplished. It provides a promising technique for high‐quality graphene process with ultra‐high flatness, and free of defects, leveraging the high surface tension of pure water. These advantages enable high‐performance device fabrication for electronic and biological research.